Chemical Characterization and Pharmacological Screening ofSome Annona Seed Oils - Joy, Beena; V. Gopi, T.; Sobhana, D. (Asian Journal of Chemistry, 2010)
Seed oils from the indigenous species, viz., Annona squamosa, Annona muricata and Annona reticulata belonging to Annonaceae family have been analyzed for their physico-chemical properties. Major fatty acids identified from Annona squamosa seed oil are palmitic acid (8.9%), linoleic acid (11%), stearic acid (1.5%), caproic acid (0.4%) and traces of caprylic acid, while in Annona muricata seed oil, caprylic acid (76%), capric acid (13%), stearic acid (10%) and traces of capric acid are present. The fatty acid constituents of Annona reticulata seed oil are linoleic acid (13%), caprylic acid (4.2%), oleic acid (0.7%), capric acid (0.26%) and traces of caproic acid. The Annona seed oils are individually screened for the acute toxicity studies and found that all the three seed oils are non-toxic. They exhibited significant antiinflammatory effects against carageenan induced paw oedema in albino rats. This is the first report of the study of chemical constituents as well as anti-inflammatory activity of annonaceous seed oils.